ANALISIS TOKSISITAS BEBERAPA TUMBUHAN HUTAN DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Zuraida (BRIN Publishing, 2018)
Utilization of forest plant seeds of suren (Toona sureni (Blume) Merr.), mimba (Azadirachta indica A.Juss.), mahogany (Swietenia mahagoni (L.) Jacq.), and saga (Adenanthera pavonina L.) for curing certain illness have long been practiced by traditional community. However, there were limited study on observing seeds bioactivity of those four species. This study aimed to analyze the toxicity activity of suren, mahoni, mimba, and saga seeds. The four seeds were initially macerated using 96% ethanol. The ethanol extracts were then tested for their toxicity effects on the Artemia salina larvae by Brine Shrimp Lethality Test (BSLT) method. BSLT results were presented through the Lethal Concentration 50 (LC50). The LC50values of ethanol extract of suren seeds, mahogany, mimba, and saga were 75, 84, 323 and 449 μg/mL, respectively. The four extracts had biological activity with LC50<1000 μg/mL, and suren seed extract was the most likely to have bioactivity because it had the lowest LC50value.